GUIDE FOR AUTHORS - Y RECURSOS AGROPECUARIOS, ECOSISTEMAS (Ecosistemas y Recursos Agropecuarios, 2015)
Ecosistemas y Recursos Agropecuarios (formerly Universidad y Ciencia) is a multi-disciplinary ma- gazine published quarterly by the Universidad Juárez Autónoma of Tabasco since 1984. It publishes original and unpublished scientific research results on the modality of Scientific Articles, Scientific Notes, Review Articles and Letters to the Editor, related to Environmental Sciences, Use and Conservation of Na- tural Resources, Animal Science, Ecology, Wild Animals and Agricultural Production. The magazine is included on the Mexican Research Magazines Index of CONACYT*, in national and international indexes and is distributed to domestic and foreign research centers and higher education institutions.